Laura Paz - Alginate-based Microcapsules for Cell Therapy: A Combination of Techniques Designed to Characterize their Stiffness and Surface Properties - Paz, Laura (Jornada de Jóvenes Investigadores del I3A, 2020)
Póster presentado en la IX Jornada de Jóvenes Investigadores del I3A